(untitled) (Bangladesh Journal of Botany, 2023)
Effects of phosphorus deficiency on ion transport and its relation with anatomical structure in mungbean plants were investigated. Phosphorous deficiency caused an increase in the accumulation of K+ in the root and a decrease in the stem and leaf of mungbean seedlings grown in solution culture. Na+ and NO3 - accumulation was increased in the root, stem and leaf of P-deficient plant. On the contrary, accumulation of PO4 3- was decreased in root, stem and leaf under P-deficiency treatment. The diameter of root was decreased under phosphorus deficiency. Vascular area was found to decrease and occupied less area with smaller size of metaxylem cavity in the root and stem of mungbean plant. In phosphorus deficient plant, phloem elements were poorly developed and occupied smaller area. Bangladesh J. Bot. 52(2): 381-387, 2023 (June)